2012
DOI: 10.1161/strokeaha.112.658849
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Recovery in Acute Ischemic Stroke Is Associated With Arterial Recanalization Grade and Speed

Abstract: Background and Purpose-Dramatic recovery (DR) is a predictor of stroke outcome among others. However, after successful recanalization, systematic favorable outcome is not the rule. We sought to analyze the impact of recanalization on DR in patients with acute ischemic stroke eligible for any revascularization strategies (either intravenous or endovascular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
3
24
0
1
Order By: Relevance
“…Previous studies found DR in 20-40% of patients with MCA strokes submitted to IV thrombolysis [1][2][3], and we hypothesize the DR frequency we found is in the lower end of this range because we also included patients with ICA occlusions.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Previous studies found DR in 20-40% of patients with MCA strokes submitted to IV thrombolysis [1][2][3], and we hypothesize the DR frequency we found is in the lower end of this range because we also included patients with ICA occlusions.…”
Section: Discussionmentioning
confidence: 67%
“…Recanalization was one of the first described independent predictors of DR, confirmed by transcranial Doppler (TCD) [1,3], angiography and MR-angiography studies [2,4], but not every patient with successful vessel recanalization after stroke achieves DR or even a good clinical outcome. Early TCD studies showed a trend for DR patients to be treated earlier [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] In this context, prompt revascularization of stroke is associated with improved outcome. [12][13][14] For instance in humans, elevated levels of vascular endothelial growth factor (VEGF) are observed after stroke, and increased microvascular density correlates with a better outcome. 15,16 In animal models, intracerebral injections of proangiogenic factors greatly enhance motor functions.…”
mentioning
confidence: 99%
“…U terapiji akutnog ishemijskog moždanog udara (AIMU) za očuvanje vitalnosti moždanog tkiva najznačajnija je brza restauracija cerebralnog krvnog protoka, koja se najčešće sprovodi intravenskom primenom rekombinantnog tkivnog aktivatora plazminogena (rtPA) u "terapijskom prozoru" od 4,5 h nakon početka simptoma (6). Uspešnost lečenja zavisi od niza faktora, a najvažniji su stepen i brzina uspostavljanja rekanalizacije i nastanak hemoragične transformacije infarkta (7). Rezultati studije koja je posmatrala ishod bolesnika lečenih intravenskom trombolizom kroz procenu neurološkog deficita, funkcionalnosti i stopu smrtnosti govore u prilog tome da je 3 meseca nakon njene primene jedna trećina bolesnika bila bez ili sa minimalnim neurološkim deficitom, 50-70% bolesnika je bilo funkcionalno nezavisno, dok je smrtnost iznosila 7-14% (8).…”
Section: Uvodunclassified